ANALYSIS OF MEDIA PROPAGANDA REPORTING THE PALESTINIAN CONFLICT ON INSTAGRAM @eye.on.palestine - Shofiyatuzzahra Shofiyatuzzahra; Anang Anas Azhar (Journal Analytica Islamica, 2025)
This study discusses how the Instagram account @eye.on.palestine acts as a digital propaganda agent in voicing the narrative of the Palestinian people's struggle through social media. This account consistently presents visual content in the form of images, videos, infographics, and narratives that depict the suffering of civilians, infrastructure damage, and symbols of struggle such as the Palestinian flag, children, and medical volunteers. This study employs a descriptive qualitative approach using content analysis to explore the digital propaganda techniques employed by the account during the period from April to June 2025. Data was collected through digital observation and documentation of the account's posts, then analyzed using the Hypodermic Needle Theory and visual communication frameworks. The results of the study show that the @eye.on.palestine account uses propaganda techniques such as emotional framing, visual persuasion, religious and nationalist symbolism, and calls for public mobilization. The content is not only informative but also has a strong persuasive and performative effect in shaping global public opinion in favor of Palestine. These findings show that social media has become a strategic space for non-state actors to build narratives of resistance and international solidarity. Additionally, high user engagement, whether in the form of comments, likes, or shares, serves as an indicator of the success of the digital propaganda constructed by this account. Thus, this study confirms that social media plays an important role in global narrative conflicts, particularly in humanitarian issues such as the Palestinian conflict.